Arabic as a Parent Language: Historical Traces in the Spread of Knowledge during the Golden Age of the Abbasids - Abidin (al-Afkar, Journal For Islamic Studies, 2025)
Arabic, which has played a crucial role in the history of civilization and science, now faces challenges in the academic and scientific world due to globalization and dialectal diversity. During the Abbasid Golden Age, Arabic became the primary language for disseminating knowledge through translation and scientific development. Therefore, the revitalization of Arabic, by exploring its glorious history, aims to re-enforce its role as the mother language. This research uses a descriptive qualitative approach with a literature review, with data collected from primary and secondary sources through academic platforms. The results of this study indicate that Arabic has a long history that began with the Semitic civilization in the Arabian Peninsula and developed rapidly during the Arab Jahiliyah period. Mecca became a trading center that introduced standard Arabic, which later became a lingua franca thanks to Islamic influence. During the Abbasid era, Arabic reached its peak as a language of knowledge with the establishment of the House of Wisdom. Its influence was also significant on Western civilization, where Arabic scientific works were translated into Latin and became an essential part of European university curricula.